Study on Temperature and Humidity Characteristics and Stability of Slopes Considering Evaporation Effect under Different Climatic Conditions - ZHANG Hao; SU Zhengyang; WANG Yakun; ZHANG Xuman (Renmin Zhujiang)
The research is conducted to study the temperature and humidity characteristics and stability laws of slopes under the action of rainfall and evaporation.Taking a mountain clay slope in a reservoir area of northeast China as an example,this study uses the locally measured climate data to build a slope model in VADOSE/W and SLOP/W modules of the software Geo-studio for finite element calculation.The results reveal that the water content of surface soil is greatly affected by evaporation,and under long-term evaporation conditions,the water content of deeper soil gradually decreases.The temperature of surface soil is greatly affected by evaporation,and as the length of evaporation time grows,the soil temperature at the same depth is higher,and the affected soil layer is deeper.The early rainfall infiltration rapidly reduces the safety factor of slope soil while the later evaporation gradually increases it.Under the evaporation effect of long-term dry weather,the safety factor gradually becomes stable,and it increases slowly after the rainfall without considering the evaporation effect.This indicates that evaporation is conducive to improving the safety factor and stability of slopes.The research results provide a reference for research on the temperature and humidity characteristics and stability of similar slopes in the reservoir areas of northeast China.